Polypyrrole-BaFe2O4 sensing layer for detection of strontium ion in aqueous solution using surface plasmon resonance curves fitting - Sadrolhosseini, A.R. (Elsevier Ltd, 2021)
The low concentration of strontium, calcium, and barium was measured with a surface plasmon resonance curve fitting technique. Polypyrrole-BaFe2O4 nanocomposite was prepared using electro-polymerization of pyrrole in the presence of magnetic nanoparticles. The thickness of the layer in the range of 6.3 and 62.2 nm the analytical methods such as Fourier transform infrared spectroscopy, energy dispersive spectroscopy, and field emission scanning electron microscopy authenticated the polypyrrole-BaFe2O4 nanocomposite formed on the surface of the gold layer. The prepared layers were used to detect and measure the low concentration of strontium, calcium, and barium ions in aqueous solution using surface plasmon resonance technique and the optical parameter, angle of resonance, resonance angle shift and affinity constant were achieved using curve fitting based on minimizing the sum of squared errors. Consequently, the degree of adsorption for the detection of strontium is about 91.3, and the sensitivity of the polypyrrole-BaFe2O4 nanocomposite layer for the detection of strontium is about 0.006Â° that is more than other ions. Â© 2021